ANALISIS WACANA KRITIS PEMBERITAAN PENATAAN TAMAN NASIONAL KOMODO PADA TRIBUNNEWS.COM DAN DETIK.COM - Muhammad Guruh Achmad Teguh; Rini Riyantini; Intan Putri Cahyani (Jurnal Pustaka Komunikasi, 2021)
The arrangement of the Komodo National Park which will turn this national park into a premium tourist destination has caused controversy between the people who disagree with the arrangement and the government. The existing arrangement is feared to disturb the habitat and the original ecosystem of the Komodo dragon and will complicate conservation activities. This controversy has increasingly attracted public attention with the appearance of photos of Komodo blocking trucks that go viral on social media. The mass media in this case also reported on this. This research was conducted to prove the alignment of the news on the arrangement of the Komodo National Park on tribunnews.com and detik.com. Which is carried out using the critical discourse analysis method on news texts in both media. This study uses a qualitative approach so that it can see more deeply the meaning behind the discourse. The research proves that the media tend to choose one party in constructing an event. Tribunnews.com proved to be in favor of the government by displaying statements submitted by the government and positive things from the arrangement. On the other hand, detik.com shows siding with the people who voice their rejection and view the existing arrangement negatively.